MEDIATING ROLE OF CUSTOMER SATISFACTION ON THE EFFECT OF SERVICE QUALITY AND INNOVATION STRATEGY TOWARD LOYALTY AT PT BANK PEMBANGUNAN DAERAH BALI - Putu Piska Pradnya Paramitha Suamba; Wayan Ardani; Luh Ketut Ayu Sudha Sucandrawati (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study aims to analyze the influence of service quality and strategic innovation on customer loyalty, with customer satisfaction as a mediating variable. Method: Employing a quantitative approach, this research utilized a survey design with 100 BPD Bali customers selected through purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS. Variables were measured based on SERVQUAL indicators for service quality, Innovation Diffusion Theory for strategic innovation, and Expectation-Confirmation Theory for satisfaction and loyalty. Results: The findings reveal that service quality and strategic innovation significantly and positively affect customer satisfaction and loyalty. Satisfaction partially mediates the relationship between service quality, strategic innovation, and loyalty. Indicators of service quality, particularly empathy, and the adoption of new technology in strategic innovation exhibited the strongest contributions. Novelty: These results underscore the importance of enhancing empathy-based services and adopting digital technologies to strengthen customer satisfaction and loyalty. PT Bank Pembangunan Daerah Bali should prioritize service reliability and product innovation to meet customer expectations.